A killer app for computer chat. (Economist, 1999)
A clever piece of software designed to imitate human responses has become useful to firms wishing to dispense information over the Internet. Designers have been developing this software since the 1960s, but it is only now that it is fulfilling a useful function. These software programs are being increasingly utilized in the area of technical support, where humans spend much of their time dealing with the same small set of easily answered questions. Existing software can more than adequately answer these menial questions, and the fact that computers do not get tired and can work around the clock is another big advantage.